Primary biliary cirrhosis associated with rheumatoid arthritis - Fan, Daiming; Han, Ying; Liu, Jingmei; Wang, Jingbo; Yan, Li; Zhou, Xinmin (Technische Universität Dortmund, 2007)
Primary biliary cirrhosis(PBC) is a slowly progressive autoimmune disease of the liver which mainly affects women aged between 35 and 45 years.Prolonged liver inflammation can cause scarring, leading to cirrhosis. Although 50 to 60 percent of patients are asymptomatic at diagnosis, they will develop symptoms later. PBC can be associated with arthralgia and other non-hepatic autoimmune diseases, such as Sjögren’s syndrome, sicca syndrome, thyroiditis and scleroderma. PBC and rheumatoid arthritis (RA) have been suggested to coexist in 1.8 to 5.6% of patients with PBC, but data supporting this association are scarce. We report two cases of such an association and discuss how to improve threapy.
two case reports in China
EXCLI Journal ; Vol. 6, 2007
Keywords: methotrexate; primary biliary cirrhosis; rheumatoid arthritis; ursodeoxycholic acid; 610